Evaluation of the presence of MMP-2, TIMP-2, BMP2/4, and TGFβ3 in the facial tissue of children with cleft lip and palate - Smane, Liene; Pilmane, Mara (Acta medica Lituanica, 2018)
Cleft lip and palate (CLP) is the most common defect affecting the face. The treatment consists of surgical reconstruction of the anatomical structures of the cleft. Part of the surgical treatment is reconstruction of the alveolar bone by means of autogenic bone grafting (osteoplasty). This study aimed to evaluate the levels of expression of extracellular matrix remodeling factors in the facial tissue of children with a complete unilateral (CU) and a complete bilateral (CB) CLP to assess whether the wound healing process is adequate. Twenty-two CLP patients were enrolled in this study. Tissue samples were collected during alveolar osteoplasty for unilateral (n = 12) or bilateral (n = 10) cleft palate, (age range from 6 years 8 months to 12 years 2 months). Control material was obtained in the case of tooth extraction (age range from 6 years 9 months to 14 years 5 months). Immunohistochemistry was used to assess the levels of matrix metalloproteinase-2 (MMP-2), tissue inhibitor of metalloproteinase-2 (TIMP-2), bone morphogenetic proteins 2 and 4 (BMP2/4), and transforming growth factor β3 (TGFβ3). Numbers of positively stained cells were graded semi-quantitatively. Data were analysed using the Kraskel-Wallis rank test and the Bonferroni correction. The total number of MMP2-positive cells was significantly lower in the CBCLP and in the control group than in the CUCLP (p < 0.001 after the Bonferroni correction). The total number of TIMP2-positive cells was significantly higher in the CUCLP than in the CBCLP and in the control group (p < 0.001; p < 0.003 after the Bonferroni correction). The overall number of BMP2/4, TGFβ3-positive cells was significantly higher in the CUCLP than in the CBCLP and in the control group (p < 0.001 after the Bonferroni correction). The decrease of the relative amount of statistically significant BMP2/4, TGFβ3, MMP-2, TIMP-2 containing bone cells in CBCLP patients identifies affected alveolar bone regeneration and remodeling process.
Keywords: cleft lip and palate; matrix metalloproteinase-2; tissue inhibitor of metalloproteinase-2; bone morphogenetic proteins 2 and 4; transforming growth factor β3